Method for producing green sheet

By limiting the compounding amount of water in the green sheet manufacturing and treating the silicon nitride water slurry under reduced pressure, the problem of excessive bubbles in the green sheet when water is used as a solvent is solved, and a high-quality silicon nitride sintered body is manufactured, with good mechanical and electrical characteristics and environmental protection.

CN116390839BActive Publication Date: 2025-04-29TOKUYAMA CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180067605.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-05
Filing Date
2021-09-29
Publication Date
2025-04-29
Estimated Expiration
2041-09-29

AI Technical Summary

Technical Problem

When water is used as the slurry solvent in the production of green sheets in the prior art, a large number of bubbles are easily generated in the green sheets, and then depressions and voids are formed on the surface of the sintered body, affecting its mechanical and electrical characteristics.

Method used

By limiting the amount of water in the silicon nitride water slurry to the range of 10 to 70 parts by mass per 100 parts by mass of silicon nitride, and the treatment is carried out under reduced pressure, the reaction between silicon nitride and water is suppressed, and the generation of bubbles is reduced.

Benefits of technology

It effectively suppresses the generation of bubbles in green sheets, improves the surface quality of the sintered body, improves its mechanical strength, electrical insulation and thermal conductivity, and meets the requirements of reducing environmental load.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004155866050000141
    Figure BDA0004155866050000141
  • Figure BDA0004155866050000142
    Figure BDA0004155866050000142
Patent Text Reader

Abstract

One embodiment of the present invention relates to a method for manufacturing a green sheet, a method for manufacturing a silicon nitride sintered body, or a green sheet molding material, wherein the method for manufacturing a green sheet includes the following steps: a step of obtaining a silicon nitride water slurry, wherein the silicon nitride water slurry contains at least silicon nitride, water, and a binder, and the amount of water added is 10 to 70 parts by mass per 100 parts by mass of silicon nitride; a decompression treatment step of decompressing the aforementioned silicon nitride water slurry to obtain a slurry for green sheet molding; and a sheet molding step of molding the aforementioned green sheet molding slurry to obtain a sheet molded body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] One embodiment of the present invention relates to a method for producing a green sheet, a method for producing a silicon nitride sintered body, or a green sheet molding material. Background Art

[0002] Among various ceramic sintered bodies, silicon nitride sintered bodies obtained by sintering silicon nitride powder at high temperature are light in weight, have strong mechanical strength from room temperature to high temperature, have excellent chemical resistance, thermal conductivity, and electrical insulation, and can be used as heat dissipation substrates, wear-resistant components, high-temperature structural components, etc.

[0003] One example of a method for producing a silicon nitride sintered body is a method of firing a sheet-shaped body called a green sheet. The green sheet can be produced by forming a silicon nitride slurry in which raw materials such as silicon nitride powder and a binder are dispersed in a solvent into a sheet using a doctor blade method or the like.

[0004] When manufacturing green sheets based on the existing doctor blade method, organic solvents such as toluene and alcohol are used as solvents for slurries from the viewpoints of ease of molding and ease of drying (for example, Patent Documents 1 and 2). For example, in Patent Document 1, green sheets are manufactured using slurry using a mixed solution of toluene and ethanol in a total of 70 parts by weight relative to 100 parts by weight of a mixed powder of silicon nitride and a sintering aid. In addition, in Patent Document 2, green sheets are manufactured using slurry with a solid content concentration of 60%, and ethanol is used as an example of a solvent.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2019-052072

[0008] Patent Document 2: Japanese Patent Application Publication No. 2020-093978 Summary of the invention

[0009] Problem that the invention aims to solve

[0010] As mentioned above, organic solvents have been used as solvents for slurries used for green sheet manufacturing in the past, but in recent years, a manufacturing method with less environmental load has been required. Therefore, the inventors have tried to use water with less environmental load than organic solvents as a solvent for slurries to manufacture green sheets. However, when water is used as the aforementioned solvent, it is shown that there is a problem of generating a large number of bubbles in the green sheets obtained. Moreover, if the green sheets with a large number of bubbles are fired, defects such as depressions and gaps will be generated on the surface of the obtained sintered body, for example, it is shown that there is a problem of not being able to obtain a good sintered body in terms of mechanical properties and electrical properties.

[0011] One embodiment of the present invention manufactures a green sheet by using water as a solvent of a slurry to reduce environmental load and suppress the generation of bubbles.

[0012] Solutions for solving problems

[0013] The inventors of the present invention have conducted in-depth research and the results show that when water is used as the solvent of the slurry, a part of the silicon nitride in the slurry reacts with water to generate gas, so a large number of bubbles are generated in the green sheet. In addition, further research has been carried out and the results show that if water is used as the solvent of the slurry, the binder will form micelles when the slurry raw materials are mixed, which will have an adverse effect on the properties of the obtained sintered body. Therefore, in order to destroy the micelles, a decompression treatment process of treating the silicon nitride water slurry under reduced pressure is required. On the other hand, it was also found that the reaction between the silicon nitride and water mainly occurs in the decompression treatment process.

[0014] Based on these insights, the present inventors studied the composition of silicon nitride water slurry that can produce raw sheets in a short period of time in order to suppress the generation of gas in the aforementioned decompression treatment process. As a result, they found that by using silicon nitride water slurry in which the amount of water in the slurry is limited to a specific range, bubbles in the raw sheets can be effectively suppressed, thus completing the present invention.

[0015] The configuration examples of the present invention are as follows.

[0016] One embodiment of the present invention is a method for manufacturing a green sheet, which includes the following steps:

[0017] A step of obtaining a silicon nitride water slurry, wherein the silicon nitride water slurry comprises at least silicon nitride, water and a binder, wherein the amount of water blended is 10 to 70 parts by mass per 100 parts by mass of silicon nitride;

[0018] a decompression treatment step of decompressing the silicon nitride water slurry to obtain a slurry for green sheet molding; and

[0019] In the sheet forming step, the green sheet forming slurry is formed to obtain a sheet formed body.

[0020] The silicon nitride water slurry preferably further contains a defoamer. The defoamer is preferably a polyether-based defoamer. The amount of the defoamer blended is preferably 0.25 to 5.0 parts by mass per 100 parts by mass of silicon nitride.

[0021] The reduced pressure treatment is preferably performed at 15° C. or higher and 55° C. or lower.

[0022] Furthermore, as one embodiment of the present invention, there is provided a method for producing a silicon nitride sintered body, the method comprising the step of firing a green sheet obtained by the above-mentioned method for producing a green sheet under the condition of 1500 to 2000°C.

[0023] Furthermore, as an embodiment of the present invention, a green sheet molding material can be cited, wherein the green sheet molding material is obtained from a silicon nitride water slurry, wherein the silicon nitride water slurry contains silicon nitride, water and a binder, and the amount of water added is 10 to 70 parts by mass per 100 parts by mass of silicon nitride.

[0024] Preferably, the silicon nitride water slurry contains a polyether-based defoamer, and the amount of the polyether-based defoamer blended is 0.25 to 5.0 parts by mass per 100 parts by mass of silicon nitride.

[0025] Effects of the Invention

[0026] According to one embodiment of the present invention, when a green sheet is manufactured using water as a solvent for a slurry, a green sheet with suppressed bubbles can be manufactured. Compared with a conventional method for manufacturing a silicon nitride sintered body using an organic solvent as a solvent for a slurry, by using the green sheet, a silicon nitride sintered body can be manufactured under manufacturing conditions with less environmental load, and a silicon nitride sintered body with good physical properties can be obtained.

[0027] Furthermore, by using water as the solvent of the slurry, there is no risk of explosion or the like due to volatilization of the residual solvent in the subsequent firing step, which is advantageous in simplifying the production equipment of the silicon nitride sintered body. DETAILED DESCRIPTION

[0028] 《Method for producing green sheet》

[0029] One embodiment of the present invention is a method for manufacturing a raw sheet, which includes the following steps: a step of obtaining a silicon nitride water slurry, wherein the silicon nitride water slurry contains at least silicon nitride, water and a binder, and the amount of water mixed is 10 to 70 parts by mass per 100 parts by mass of silicon nitride; a decompression treatment step of decompressing the aforementioned silicon nitride water slurry to obtain a slurry for raw sheet molding; and a sheet molding step of molding the aforementioned slurry for raw sheet molding to obtain a sheet molding body.

[0030] <Step of Obtaining Silicon Nitride Aqueous Slurry>

[0031] The step of obtaining silicon nitride water slurry is a step of obtaining silicon nitride water slurry containing at least silicon nitride, water, and a binder, wherein the blending amount of water is 10 to 70 parts by mass per 100 parts by mass of silicon nitride.

[0032] 〔Silicon Nitride〕

[0033] The silicon nitride water slurry contains silicon nitride. As the silicon nitride water slurry containing silicon nitride, it is preferable to use silicon nitride powder as its raw material.

[0034] The silicon nitride powder mixed in the silicon nitride water slurry is not particularly limited as long as it is a powdery substance represented by the chemical formula Si3N4, and a known powder can be used. For example, the silicon nitride powder can be a powder containing α-Si3N4 particles, or a powder containing β-Si3N4 particles, or a powder containing both. It is particularly preferred to use a silicon nitride powder containing 80% or more, especially 90% or more of β-Si3N4 particles.

[0035] The silicon nitride powder to be blended in the silicon nitride water slurry may be one kind or two or more kinds.

[0036] The specific surface area of ​​the silicon nitride powder mixed in the silicon nitride water slurry is preferably 5 m 2 / g or more and preferably 20m 2 / g or less.

[0037] The specific surface area of ​​silicon nitride powder is less than 5m 2 On the other hand, if the specific surface area exceeds 20 m 2 / g, a reaction with water is likely to occur when preparing the slurry described later. In addition, bubbles are likely to be incorporated into the obtained slurry, and a long time is required for degassing. As a result, there is a tendency for the amount of bubbles in the obtained green sheet to increase.

[0038] The specific surface area of ​​the silicon nitride powder is more preferably 7 m 2 / g or more, more preferably 15m 2 It should be noted that the specific surface area in this specification refers to the BET specific surface area measured using the BET one-point method based on nitrogen adsorption.

[0039] 〔water〕

[0040] The silicon nitride water slurry uses water as a solvent. By using water as a solvent for the silicon nitride water slurry, the environmental load can be reduced compared to the case of using an organic solvent.

[0041] The water is not particularly limited, and tap water or the like may be used, but pure water, ion-exchanged water or the like is preferably used.

[0042] The amount of water in the silicon nitride water slurry is 10 parts by mass or more, preferably 30 parts by mass or more and 70 parts by mass or less, preferably 50 parts by mass or less per 100 parts by mass of silicon nitride. By limiting the amount of water to 70 parts by mass or less, bubbles can be effectively suppressed from remaining in the green sheet.

[0043] As described above, the reason why bubbles can be suppressed from remaining in the green sheet by setting the blending amount of water in the silicon nitride water slurry to 10 to 70 parts by mass is not clear, but the present inventors consider it as follows.

[0044] That is, it is believed that if the amount of water in the silicon nitride water slurry containing a binder is limited to 10 to 70 parts by mass, the concentration of the binder present on the surface of silicon nitride and between silicon nitrides becomes higher, and the contact opportunity between silicon nitride and water can be suppressed. Moreover, as a result, it is speculated that the generation of gases such as ammonia generated by the reaction of silicon nitride and water can be suppressed, and bubbles generated by the generation of gas can also be suppressed.

[0045] In addition, it is speculated that in the above-mentioned slurry, since the molecules of the binder are dispersed in water, micelles containing bubbles are easily formed, and a decompression treatment process is required to remove them, but by limiting the amount of water blended, the amount of micelles generated can be suppressed. By suppressing the amount of micelles generated, the decompression treatment process can be completed in a shorter time, and as a result, it is speculated that the generation of gas in the decompression treatment process can be suppressed.

[0046] 〔Binder〕

[0047] The silicon nitride aqueous slurry is mixed with a binder. By mixing the binder, the sheet molded body obtained from the silicon nitride aqueous slurry can be easily maintained in a desired shape.

[0048] As the binder, an organic polymer is preferably used, and examples thereof include polyvinyl alcohol, polyvinyl butyral, methyl cellulose, alginic acid, polyethylene glycol, carboxymethyl cellulose, ethyl cellulose, and acrylic resins.

[0049] The binder to be blended in the silicon nitride aqueous slurry may be one kind or two or more kinds.

[0050] The amount of the binder in the silicon nitride aqueous slurry is preferably 1 to 30 parts by mass per 100 parts by mass of silicon nitride, and the amount can be appropriately determined depending on molding conditions and the like.

[0051] 〔additive〕

[0052] The silicon nitride aqueous slurry may contain known additives within a range not hindering the effects of the present invention.

[0053] The additives that can be blended in the silicon nitride aqueous slurry may be either one kind or two or more kinds.

[0054] [Sintering aid]

[0055] It is preferred that a sintering aid be blended into the silicon nitride water slurry.

[0056] The sintering aid is not particularly limited as long as it is used for sintering the silicon nitride powder. However, compounds containing no oxygen atom are particularly preferably used from the viewpoint of suppressing a decrease in the thermal conductivity of the obtained silicon nitride sintered body.

[0057] As the aforementioned compound not containing oxygen atoms, carbonitride compounds containing rare earth elements or magnesium elements (hereinafter also referred to as "specific carbonitride compounds") and nitride compounds containing magnesium elements (hereinafter also referred to as "specific nitride compounds") are preferred. By using one or more compounds selected from the group consisting of specific carbonitride compounds and specific nitride compounds as sintering aids, a silicon nitride sintered body with high thermal conductivity can be obtained more effectively and easily. It is believed that the aforementioned specific carbonitride compound functions as a getter that adsorbs oxygen that may be contained in the silicon nitride powder mixed in the silicon nitride water slurry, and it is believed that the aforementioned specific nitride compound can reduce the total oxygen content of the silicon nitride sintered body. As a result, it is believed that by using one or more compounds selected from the group consisting of specific carbonitride compounds and specific nitride compounds, a silicon nitride sintered body with higher thermal conductivity can be obtained.

[0058] The specific carbonitride-based compound and the specific nitride-based compound may be used alone or in combination of two or more.

[0059] As the rare earth element, Y (yttrium), La (lanthanum), Sm (samarium), Ce (cerium), Yb (ytterbium) and the like are preferred.

[0060] Examples of carbonitride compounds containing rare earth elements include Y2Si4N6C, Yb2Si4N6C, and Ce2Si4N6C. Among these, Y2Si4N6C and Yb2Si4N6C are preferred because they can easily produce silicon nitride sintered bodies with high thermal conductivity.

[0061] Examples of carbonitride compounds containing magnesium include MgSi4N6C.

[0062] In addition, as a nitride-based compound containing the magnesium element, MgSiN 2 can be cited, for example.

[0063] Among the aforementioned specific carbonitride compounds and specific nitride compounds, particularly preferred compounds are Y2Si4N6C, MgSi4N6C, and MgSiN2.

[0064] In addition, it is preferable to use a metal oxide as a sintering aid together with the compound not containing an oxygen atom. By using a metal oxide as a sintering aid, the sintering of silicon nitride becomes easier, and a denser and stronger sintered body can be easily obtained.

[0065] Examples of the metal oxide include yttrium oxide (Y2O3), magnesium oxide (MgO), and cerium oxide (CeO2). Among these, yttrium oxide is preferred.

[0066] The metal oxide may be used alone or in combination of two or more.

[0067] When a compound containing no oxygen atoms and a metal oxide are used together as sintering aids, the mass ratio of the compound containing no oxygen atoms to the metal oxide (compound containing no oxygen atoms / metal oxide) is preferably greater than 0.2, more preferably greater than 0.4, further preferably greater than 0.6 and preferably less than 4, more preferably less than 2.

[0068] When the mass ratio is within such a range, a dense silicon nitride sintered body with high thermal conductivity can be easily obtained.

[0069] When a sintering aid is added to the silicon nitride water slurry, the amount of the sintering aid in the silicon nitride water slurry is preferably 5 parts by mass or more, more preferably 7 parts by mass or more and preferably 20 parts by mass or less, more preferably 10 parts by mass or less per 100 parts by mass of silicon nitride.

[0070] [Defoaming agent]

[0071] A defoaming agent may be mixed into the silicon nitride water slurry.

[0072] By adding a defoaming agent, bubbles caused by the gas generated by the reaction between silicon nitride and water can be easily destroyed, and the generation of bubbles in the green sheet can be more highly suppressed. In addition, the defoaming agent can also destroy bubbles generated by the incorporation of external air during the green sheet manufacturing operation such as stirring and molding, so it is easy to more highly suppress the generation of bubbles in the green sheet.

[0073] A known defoaming agent can be used as the defoaming agent, and a polyether-based defoaming agent is preferably used.

[0074] Examples of the polyether defoaming agent include: polyoxyalkylenes such as (poly)oxyethylene and (poly)oxypropylene; (poly)oxyalkylene alkyl ethers such as diethylene glycol heptyl ether, polyoxyethylene oleyl ether, polyoxypropylene butyl ether, polyoxyethylene polyoxypropylene 2-ethylhexyl ether; (poly)oxyalkylene (alkyl) aromatic ethers such as polyoxypropylene phenyl ether and polyoxyethylene nonylphenyl ether; acetylene ethers such as 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 2,5-dimethyl-3-hexyne-2,5-diol, and 3-methyl-1-butyne-3-ol (Poly)oxyalkylene fatty acid esters such as diethylene glycol oleate, diethylene glycol laurate, and ethylene glycol distearate; (Poly)oxyalkylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate and polyoxyethylene sorbitan trioleate; (Poly)oxyalkylene alkyl (aryl) ether sulfates such as polyoxypropylene methyl ether sodium sulfate and polyoxyethylene dodecylphenol ether sodium sulfate; (Poly)oxyalkylene phosphate alkyl esters such as (Poly)oxyethylene stearyl phosphate; (Poly)oxyalkylene alkylamines such as polyoxyethylene laurylamine.

[0075] When a defoaming agent is added to the silicon nitride water slurry, the amount of the defoaming agent is not particularly limited, but is preferably 0.25 parts by mass or more, more preferably 0.5 parts by mass or more, and preferably 5.0 parts by mass or less, more preferably 2.0 parts by mass or less per 100 parts by mass of silicon nitride.

[0076] [Organic solvents]

[0077] In the silicon nitride aqueous slurry, an organic solvent other than water, such as alcohol, may also be used as a solvent, but from the perspective of environmental load, the amount of the organic solvent is preferably as small as possible, preferably 50% or less of the amount of the aforementioned solvent, more preferably 20% or less, and even more preferably 1% or less.

[0078] [Method for producing silicon nitride aqueous slurry]

[0079] The method for manufacturing the silicon nitride water slurry is not particularly limited, for example, each component can be measured in a specified blending amount, and the silicon nitride powder can be dispersed in a solvent for stirring and mixing. As a dispersing device for stirring and mixing, for example, an ultrasonic dispersing device, a bead mill, a roller mill, a homogenizer, an Ultra Mixer, a dispersing mixer, a through-type high-pressure dispersing device, a collision-type high-pressure dispersing device, a porous high-pressure dispersing device, a crushing-type high-pressure dispersing device, a (collision+through) type high-pressure dispersing device, and an ultrahigh-pressure homogenizer can be cited. In addition, after stirring and mixing, as needed, operations such as filtering by a filter can be performed to remove the coarse particles in the slurry.

[0080] <Decompression treatment process>

[0081] In the decompression treatment step, the silicon nitride water slurry is decompressed to obtain a slurry for green sheet molding.

[0082] The reduced pressure treatment step is performed by allowing the silicon nitride water slurry to exist under reduced pressure conditions lower than the atmospheric pressure (eg, -0.20 MPa·G or higher, eg, -0.08 MPa·G or lower).

[0083] The decompression treatment process can destroy the micelles of the micellized binder, and the occurrence of defects on the surface of the sintered body obtained by firing the green sheet can be suppressed. In addition, as mentioned above, by making the amount of water mixed in the silicon nitride water slurry 10 to 70 parts by mass, the contact opportunity between silicon nitride and water is reduced, and the amount of micelles generated in the slurry is reduced. Therefore, it is speculated that the decompression treatment process can be completed in a short time, and the generation of gas caused by the reaction between silicon nitride and water, which is the cause of bubbles in the green sheet, can be suppressed.

[0084] The pressure in the reduced pressure treatment step is preferably -0.15 MPa·G or higher and preferably -0.09 MPa·G or lower.

[0085] If the pressure is too low, there is a concern that new bubbles may be generated due to sudden boiling, etc. If the pressure is too high, it tends to be difficult to fully destroy the micelles in a short period of time.

[0086] The temperature of the reduced pressure treatment step is not particularly limited as long as the silicon nitride aqueous slurry maintains fluidity, but is preferably 15°C or higher, more preferably 20°C or higher, further preferably 25°C or higher, and is preferably 55°C or lower, more preferably 45°C or lower.

[0087] The lower the temperature of the decompression treatment process, the worse the micelle destruction efficiency becomes. Therefore, the decompression treatment process must be performed for a long time, but the reactivity of silicon nitride with water also becomes lower, and the amount of gas generated per unit time can be reduced. On the other hand, the higher the temperature of the decompression treatment process, the higher the reactivity of silicon nitride with water, the greater the amount of gas generated per unit time, but the time of the decompression treatment process can be shortened. Due to these balances, by performing the decompression treatment process within the above-mentioned temperature range, it becomes easy to effectively suppress the generation of bubbles in the green sheet.

[0088] The preferred time of the decompression treatment step varies depending on the temperature of the decompression treatment. From the viewpoint of fully destroying micelles and suppressing the generation of gas caused by the reaction between silicon nitride and water, it is preferably 1 hour or more and preferably 5 hours or less. When the temperature during the decompression treatment is 25° C. or more, the time of the decompression treatment step is particularly preferably 3 hours or less.

[0089] In the decompression treatment step, water as a solvent is removed depending on the conditions, and the viscosity of the slurry (slurry for green sheet molding) after the decompression treatment step may be different from that of the silicon nitride water slurry. In this case, the decompression treatment step can destroy the micelles and adjust the viscosity of the green sheet molding slurry to be suitable for molding.

[0090] From the viewpoint of moldability, the viscosity of the green sheet molding slurry at 23° C. is preferably 1000 mPa·s or more, more preferably 3000 mPa·s or more, and is preferably 10000 mPa·s or less, more preferably 7000 mPa·s or less.

[0091] It should be noted that the viscosity is a value measured by a rotational viscometer.

[0092] The solid content concentration of the green sheet molding slurry is preferably 65 to 75% from the viewpoint of moldability and facilitation of the drying step described later.

[0093] 《Green Sheet Molding Materials》

[0094] The green sheet molding material according to one embodiment of the present invention is not particularly limited as long as it is obtained from the above-mentioned silicon nitride water slurry.

[0095] A suitable specific example of the green sheet molding material is the aforementioned silicon nitride water slurry or the aforementioned green sheet molding slurry.

[0096] <Sheet forming process>

[0097] The sheet forming step of forming the green sheet forming slurry to obtain a sheet forming body is not particularly limited, and a known forming method can be used. However, forming by a doctor blade method is preferred from the viewpoint of obtaining a sheet forming body with good uniformity in thickness.

[0098] The sheet compact formed as described above may be used as a green sheet, but it is preferably formed into a green sheet by subjecting the sheet compact formed as described above to a drying step of drying the sheet compact formed as described above.

[0099] The drying step is a step of removing water from the sheet molded body formed as described above. By performing the drying step, the degreasing step and the calcining step described later can be easily performed.

[0100] The drying step can be performed, for example, by leaving the sheet molded body at a temperature of about 30 to 150°C.

[0101] In the drying step, the green sheet is preferably dried so that the moisture content of the obtained green sheet becomes 10% or less.

[0102] The obtained green sheet can be processed into an appropriate size, an arbitrary shape, etc. as required. As such a size and shape, for example, it is usually processed into a substantially rectangular parallelepiped shape with a side of 100 to 2000 mm and a thickness of 0.3 to 1.2 mm.

[0103] Furthermore, it is preferred that the obtained green sheet be subjected to a degreasing step as necessary before the firing step described later.

[0104] As an example of the degreasing step, there is a step of heating the sheet compact for the purpose of removing organic substances such as a binder from the green sheet.

[0105] The heating temperature in the degreasing step is usually 300° C. or higher, preferably 400° C. or higher, and usually 1200° C. or lower, preferably 1000° C. or lower.

[0106] The heating time of the green sheet in the degreasing step can be appropriately selected depending on the type of binder and the degreasing atmosphere, and is usually 30 minutes or more, preferably 2 hours or more, and usually 140 hours or less, preferably 120 hours or less.

[0107] The degreasing process is usually performed in an atmosphere of an oxidizing gas such as oxygen or air, a reducing gas such as hydrogen, an inert gas such as argon or nitrogen, carbon dioxide, or a mixed gas thereof, or in an atmosphere of a humidified gas containing a mixture of these gases and water vapor.

[0108] 《Silicon nitride sintered body》

[0109] The silicon nitride sintered body according to one embodiment of the present invention can be obtained by firing the green sheet obtained by the above-mentioned method for producing a green sheet (firing step).

[0110] The firing conditions are not particularly limited, and the firing may be carried out under known firing conditions for obtaining a silicon nitride sintered body.

[0111] The calcination is usually performed in an inert gas atmosphere, such as a nitrogen atmosphere or an argon atmosphere.

[0112] The calcination is preferably performed in a pressure-controlled atmosphere.

[0113] The pressure at this time is not particularly limited. At low pressure, silicon nitride may decompose during sintering, and at high pressure, equipment and other costs are increased. Therefore, the pressure is, for example, 0 MPa·G or more, for example, 10 MPa·G or less, preferably 3 MPa·G or less, and more preferably 0.1 MPa·G or less.

[0114] The calcination temperature is not particularly limited as long as the desired sintering reaction proceeds, but is usually 1200°C or higher, preferably 1500°C or higher, and usually 2000°C or lower, preferably 1800°C or lower.

[0115] The calcination time is not particularly limited as long as the desired sintering reaction proceeds, but is generally about 3 to 20 hours.

[0116] The silicon nitride sintered body manufactured as described above is a sintered body obtained by using water as a solvent of the slurry used in the manufacture of the green sheet, and the occurrence of defects such as surface depressions and internal voids caused by bubbles generated during the manufacture of the green sheet is suppressed. Moreover, the silicon nitride sintered body in which defects such as surface depressions and voids are suppressed has good physical properties such as mechanical properties and electrical properties.

[0117] The three-point bending strength (measured in accordance with JIS R 1601), which is an indicator of the mechanical strength of the silicon nitride sintered body, is preferably 500 MPa or more, more preferably 550 MPa or more.

[0118] A silicon nitride sintered body in which defects such as surface depressions and internal voids are suppressed tends to have a three-point bending strength within the above-mentioned range, and therefore has excellent reliability as a product.

[0119] The dielectric breakdown voltage of the silicon nitride sintered body is preferably 11 kV or more, more preferably 13 kV or more.

[0120] The silicon nitride sintered body having such a breakdown voltage is unlikely to undergo a breakdown and is excellent in reliability as a product.

[0121] The thermal conductivity of the silicon nitride sintered body is preferably 60 W / m·K or more, more preferably 75 W / m·K or more.

[0122] The thermal conductivity can be measured by a laser flash method.

[0123] The uses of silicon nitride sintered bodies are not particularly limited, and examples thereof include various heat dissipation substrates, power module substrates (for vehicles, electric railways, and high-power semiconductors), high-frequency circuit substrates, LED packages, optical pickup bases (for DVDs and CDs), materials for engines or gas turbines, turbocharger rotors, glow plugs for diesel engines, thermal spark plugs, heater tubes, rods for low-pressure casting, galvanic protection tubes, exhaust gas injection tubes, heat-resistant and / or impact-resistant components, polishing cloth correction platforms, high-frequency quenching jigs, jigs for vehicle body assembly and / or engine manufacturing, jigs for pressurization processes, insulating components, insulating medical devices and / or surgical instruments, and rollers for plastic processing.

[0124] Example

[0125] Hereinafter, one embodiment of the present invention will be specifically described based on examples, but the present invention is not limited to these examples. Each test method is as follows.

[0126] <Evaluation of bubbles in green sheets>

[0127] The surfaces of 10 green sheets (300 mm×2000 mm×0.4 mm) produced under the same conditions and having the same shape were visually observed, the number of depressions per sheet (average value of the number of depressions) was calculated, and evaluation was performed according to the following evaluation criteria.

[0128] (Evaluation Criteria)

[0129] A: The number of depressions per green sheet is less than 10

[0130] B: The number of depressions per green sheet is 10 or more and less than 20

[0131] C: The number of depressions per green sheet is 20 or more and less than 30

[0132] D: The number of depressions per green sheet is 30 or more and less than 40

[0133] E: The number of depressions per green sheet is 40 or more

[0134] <Evaluation of sintered body surface properties>

[0135] The surfaces of 10 sintered bodies (300 mm×2000 mm×0.4 mm) produced under the same conditions and having the same shape were visually observed, the number of depressions per body (average value of the number of depressions) was calculated, and evaluation was performed according to the following evaluation criteria.

[0136] (Evaluation Criteria)

[0137] A: The number of depressions per sintered body is less than 10

[0138] B: The number of depressions per sintered body is 10 or more and less than 20

[0139] C: The number of depressions per sintered body is 20 or more and less than 30

[0140] D: The number of depressions per sintered body is 30 or more and less than 40

[0141] E: The number of depressions per sintered body is 40 or more

[0142] The raw materials and their abbreviations used in the tests are shown below.

[0143] <Silicon nitride powder>

[0144] C1: Surface area 12m 2 / g β-Si3N4 powder

[0145] <Sintering aid>

[0146] S1: Yttrium oxide (specific surface area 20m 2 / g)

[0147] ·S2: Magnesium silicon nitride (specific surface area 12m 2 / g)

[0148] <Binder>

[0149] B1: Acrylic resin emulsion (manufactured by Fujikura Chemicals Co., Ltd.: Acrybase EMK-02)

[0150] <Defoaming agent>

[0151] (Polyether defoamer)

[0152] ·D1: Polyoxyalkylene (manufactured by SAN NOPCO LIMITED: SN Defoamer 485)

[0153] <Example 1>

[0154] 100 g of silicon nitride powder C1, 5.6 g of sintering aid S1, 3.4 g of sintering aid S2, 124 g of binder B, 0.5 g of defoamer D1, and 47 g of water were mixed and stirred for 48 hours to obtain a silicon nitride water slurry. The obtained silicon nitride water slurry was put into a container, a reduced pressure state of -0.1 MPa·G was formed in the container, and it was allowed to stand at 30°C for 2.5 hours to perform a reduced pressure treatment process to obtain a slurry for green sheet molding. After the obtained green sheet molding slurry was passed through a polyethylene net (pore size 229 μm) to remove coarse particles, the obtained slurry was used to make a 300 mm × 2000 mm × 0.4 mm sheet molding by a doctor blade method. The obtained sheet molding was placed on a plate heater set at 50°C, left to stand for 3 hours and dried to obtain a green sheet. The obtained green sheet was evaluated for bubbles, degreased at 500°C for 60 hours, and then fired at 1800°C and 0.1 MPa·G in a nitrogen atmosphere for 16 hours to obtain a silicon nitride sintered body. Thereafter, the surface properties of the obtained silicon nitride sintered body were evaluated. The composition of the silicon nitride water slurry and the conditions of the decompression treatment process are shown in Table 1, and the evaluation results of the obtained green sheet and silicon nitride sintered body are shown in Table 2.

[0155] <Examples 2 to 5, Comparative Examples 1 to 3>

[0156] Evaluation was performed in the same manner as in Example 1 except that the composition of the silicon nitride water slurry and the decompression treatment step conditions were changed as shown in Table 1. In Comparative Example 3, the silicon nitride water slurry was not subjected to the decompression treatment step.

[0157] Table 1 shows the composition of the silicon nitride water slurry and the conditions of the reduced pressure treatment step. Table 2 shows the evaluation results of the obtained green sheet and silicon nitride sintered body.

[0158] [Table 1]

[0159]

[0160] [Table 2]

[0161]

[0162] In the above examples, the green sheet molding slurry obtained by the production method of Examples 1 to 5 had a solid content concentration of 65 to 75% and a viscosity of 4000 to 6000 mPa·s at 23° C. The viscosity is a value measured by a rotational viscometer.

[0163] Compared with Comparative Examples 1 and 2 with high water content, Examples 1 to 5 of one embodiment of the present invention produced green sheets with fewer bubbles, and as a result, good sintered bodies were obtained. It should be noted that Comparative Example 3 with low water content could not be formed into a green sheet itself.

Claims

1. A method for producing a green sheet, comprising the following steps: The step of obtaining a silicon nitride water slurry, wherein the silicon nitride water slurry comprises at least silicon nitride powder, water and a binder, wherein the amount of water blended is 10 to 70 parts by mass per 100 parts by mass of the silicon nitride powder; a decompression treatment step of decompressing the silicon nitride water slurry to obtain a slurry for green sheet molding, wherein the viscosity of the slurry for green sheet molding at 23° C. is greater than or equal to 3000 mPa·s and less than or equal to 10000 mPa·s; and a sheet forming step of forming the green sheet forming slurry to obtain a sheet forming body, The BET specific surface area of ​​the silicon nitride powder measured by the BET 1 point method based on nitrogen adsorption is 5 m 2 / g or more and 20m 2 / g or less, The binder is at least one selected from methyl cellulose, alginic acid, polyethylene glycol, carboxymethyl cellulose, ethyl cellulose, and acrylic resin.

2. The method for producing a green sheet according to claim 1, wherein: The silicon nitride water slurry further comprises a defoaming agent.

3. The method for producing a green sheet according to claim 2, wherein: The defoamer is a polyether defoamer.

4. The method for producing a green sheet according to claim 2, wherein: The amount of the defoaming agent blended is 0.25 to 5.0 parts by mass per 100 parts by mass of the silicon nitride powder.

5. The method for producing a green sheet according to any one of claims 1 to 4, wherein: The reduced pressure treatment is performed at 15° C. or higher and 55° C. or lower.

6. A method for producing a silicon nitride sintered body, comprising the following steps: The green sheet obtained by the method for producing a green sheet according to any one of claims 1 to 5 is fired at 1500 to 2000°C.

7. A green sheet molding material, which is obtained from a silicon nitride water slurry, wherein the silicon nitride water slurry comprises silicon nitride powder, water and a binder, wherein the amount of water blended is 10 to 70 parts by mass per 100 parts by mass of the silicon nitride powder, and the silicon nitride water slurry is subjected to a decompression treatment to obtain a green sheet molding slurry, wherein the viscosity of the green sheet molding slurry at 23° C. is greater than or equal to 3000 mPa·s and less than or equal to 10000 mPa·s, The BET specific surface area of ​​the silicon nitride powder measured by the BET 1 point method based on nitrogen adsorption is 5 m 2 / g or more and 20m 2 / g or less, The binder is at least one selected from methyl cellulose, alginic acid, polyethylene glycol, carboxymethyl cellulose, ethyl cellulose, and acrylic resin.

8. The green sheet molding material according to claim 7, wherein The silicon nitride water slurry contains a polyether defoamer, The amount of the polyether-based defoamer blended is 0.25 to 5.0 parts by mass per 100 parts by mass of the silicon nitride powder.

Citation Information

Patent Citations

  • Silicon nitride sintered substrate, electronic apparatus, and method for manufacturing the silicon nitride sintered substrate

    JP2019052072A

  • Method for manufacturing sintered silicon nitride substrate

    JP2020093978A

  • Silicon nitride powder

    JP1996133709A

  • Ceramics green sheet and method of producing the same

    JP2008169050A

  • Slurry composition for ceramic green sheet

    JP2013170106A